Optimizing building performance with Digital Twins: Pathways to energy efficiency and decarbonization - Tanase Andra; Croitoru Cristiana (E3S Web of Conferences)
In the context of current energy consumption and CO2 emissions, the impact of buildings is highly significant. In the quest for sustainable building management, the concept of digital twins emerges as a transformative technology, offering unprecedented capabilities for enhancing energy efficiency and reducing carbon footprints. This article explores the application of digital twins in the built environment, emphasizing their role in achieving significant energy and environmental benefits. Beginning with a brief discussion introducing the concept of digital twins, the article highlights their critical importance in modern building management and their potential to revolutionize sustainability practices. It then examines the role of IoT and AI in enabling advanced aspects of digital twin technology, including its technological functionalities. A comparative analysis of different simulation tools and methodologies follows, providing a comprehensive overview of how digital twins can be utilized to optimize building performance.